A 3D‐printed polycaprolactone/β‐tricalcium phosphate mandibular prosthesis: A pilot animal study. (12th March 2019) - Park, Jae Hong; Jung, Soo Yeon; Lee, Chi‐Kyou; Ban, Myung Jin; Lee, Sang Jin; Kim, Ha Yeong; Oh, Hyun Ju; Kim, Byeong Kook; Park, Hae Sang; Jang, Si‐Hyong; Kim, Han Su
Abstract : Objective: In this study, we assessed the effectiveness of a tonsil‐derived mesenchymal stem cell (TMSC)‐transplanted polycaprolactone/beta‐tricalcium phosphate prosthesis (specifically designed for easier fixing and grafting with a single scaffold) on rabbit mandible osteogenesis. Methods: The mandibles of 18 rabbits were exposed, and 10 × 8‐mm bone defects were made. Two rabbits did not receive implants; four were reconstructed with the scaffold control (SC) (SC group); four were reconstructed with scaffolds soaked in peripheral blood (PB) (PB group); four were reconstructed with TMSC‐transplanted scaffolds (TMSC group); and four were reconstructed with differentiated osteocyte‐transplanted scaffolds (DOC) (DOC group). Each rabbit was sacrificed 12 weeks after surgery, and the area of new bone formation was investigated by mechanical testing, histology, and micro‐computed tomography. Results: More extended and denser new bone masses were observed in the TMSC and DOC groups, although fibrosis and vascular formation levels were similar in all groups, suggesting that the dual‐structured scaffold alone provides a good environment for bone attachment and regeneration. The bone volumes of representative scaffolds from the SC, PB, TMSC, and DOC groups were 43.12, 48.35, 53.10, and 57.44% of the total volumes, respectively. Conclusion: The design of the scaffold resulted in effective osteogenesis, and TMSCs showed osteogenic potency, indicating that their combination could enable effective bone regeneration. Level of Evidence: NA Laryngoscope, 130:358–366, 2020